Gastric volvulus Different forms of presentation - Pagán, Alberto; García, Mario; García, Ramón; Ferra, Sebastián; Soro, José Antonio (Cirugía del Uruguay, 1998)
Gastríc volvulus is an ínfrequent entíty wíth mu/tiple presentations whích make different clínica! expressíons of gastríc volvu/us and dífferent treatment optíons both far chronícal ar acute forms and discusses díagnostíc díffícu/tíes and how they can condítíon the therapeutíca/ performance.